Assessment of childhood obesity in secondary care: OSCA consensus statement. Issue 3 (18th May 2012) - Viner, Russell M; White, Billy; Barrett, Timothy; Candy, David C A; Gibson, Penny; Gregory, John W; Matyka, Krystyna; Ong, Kenneth; Roche, Edna; Rudolf, Mary C J; Shaikh, Guftar; Shield, J P; et al.
Abstract : This expert opinion provides detailed guidance on assessing obesity in secondary paediatric practice. This guidance builds on existing recommendations from National Institute of Health and Clinical Excellence in the UK, and is evidence based where possible. Guidance is provided on which obese children and young people are appropriate to be seen in secondary care and relevant history and investigations, and guidance on when further investigation of causes and obesity-related comorbidity is appropriate.